SOUTHERN HONOR: AN ANALYSIS USING AMERICAN STUDIES THEORY - Basuki, Imam (Universitas Muhammadiyah Jember, 2017)
The goal of this article is to discussÂ Southern Honor,Â the work written by Brown using American Studies Approach/ theory. American Studies is an interdisciplinary discipline comprising of social science, humanities, history, art, economics, sociology, anthropology, politics, religion, and law. In American studies method, a researcher, for instance â€“ from a discipline of historical science- in collecting data, he or she does not only use data from history but also from a literary work like novel or drama because a literary work was a mental fact of society at that time This makes American Studies different from the other disciplines.Â Southern HonorÂ by Brown is an example of work written by American Studies approach using three principal theories of American Studies such as: 1. Reconciliation of Tenses (Past, Present, Future); 2. Reconciliation of Academic discipline (Anthropology, Economy, Politics, Sociology, Psychology, Literature, and History); 3. Reconciliation of Region, Nation, and World. For the theory of number 3 starting from something micro namely â€œHonorsâ€ in the society of southern America like â€œgentleâ€, â€œoathâ€, possession of wealth, and so on can explain more detail about America. The result of this research proves that â€œHonorâ€ does not only give influence on the ethic and behavior of southern American society at that time, before civil war, but also provide influence on all aspects of life of American society as a whole up to now.